Can shear wave imaging distinguish between diffuse interstitial and replacement myocardial fibrosis?. (8th February 2021) - Petrescu, ANIELA; Cvijic, M; Bezy, S; Santos, P; Duchenne, J; Orlowska, M; Pedrosa, J; Degtiarova, G; Van Keer, J; Von Bardeleben, S; Droogne, W; Van Cleemput, J; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background:   Diffuse interstitial or myocardial replacement fibrosis are common features of a large variety of cardiomyopathies. These alterations contribute to functional changes, particularly to an increased myocardial stiffness (MS). Histological examination is the gold standard for myocardial fibrosis quantification, however, it requires endomyocardial biopsy which is invasive and not without risks. Cardiac magnetic resonance (CMR) can characterize the extent of both diffuse and replacement fibrosis and may have prognostic value in various cardiomyopathies. Echocardiographic shear wave (SW) elastography is an emerging approach for measuring MS in vivo. SWs occur after mechanical excitation of the myocardium, e.g. after mitral valve closure (MVC), and their propagation velocity is directly related to MS, thus providing an opportunity to assess stiffness at end-diastole. Purpose: The aim was to investigate if velocities of natural SW can distinguish between interstitial and replacement fibrosis.  Methods: We prospectively enrolled 47 patients (22 patients after heart transplant [54.2 ± 15.8 years, 82.6% male] and 25 patients with established hypertrophic cardiomyopathy [54.0 ± 13.5 years, 80.0% male]) undergoing CMR during their check-up. We performed SW elastography in parasternal long axis views of the LV using a fully programmable experimental scanner (HD-PULSE) equipped with a clinical phased array transducer (Samsung Medison P2-5AC) at 1100 ± 250 frames per second. Tissue acceleration maps were extracted from an anatomical M-mode line along the midline of the LV septum. The SW propagation velocity at MVC was measured as the slope in the M-mode image. All patients underwent T1 mapping as well as late gadolinium enhancement (LGE) cardiac magnetic resonance at 1.5 T to assess the presence of diffuse or replacement fibrosis (Figure A). Therefore, patients were divided in three groups: no fibrosis, diffuse fibrosis and replacement fibrosis. Results: Mechanical SW's were observed in 46 subjects starting immediately after MVC and propagating from the LV base to the apex. SW propagation velocity at MVC correlated well with native myocardial T1 values (r = 0.65, p < 0.0001) and differed significantly among groups (p < 0.0001), with a significant post-test between any pair of groups (Figure B). SW velocities below a cut-off of 6.01 m/s showed the highest accuracy to identify patients without any type of fibrosis (sensitivity 88 %, specificity 89%, area under the curve = 0.93) (Figure C). A cut-off of 8.11 m/s could distinguish replacement fibrosis from diffuse fibrosis with a sensitivity and specificity of 59% and 92 %, respectively (area under the curve = 0.80) (Figure D). Conclusions:   Shear wave velocities after mitral valve closure can distinguish between normal and pathological myocardium and can detect differences between diffuse and replacement fibrosis.